PENINGKATAN PENGETAHUAN MELALUI EDUKASI DALAM UPAYA MENGATASI ANEMIA PADA REMAJA PUTRI - Naomi, Anggie Rapita; Yovi, Maria; Manik, Yustrisa (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
One of the health problems in developed countries including Indonesia is the problem of nutrition in the form of micronutrient deficiencies such as anemia. Anemia is a condition of the body where the hemoglobin (Hb) level in the blood is lower. Based on the latest data from the 2023 Indonesian Health Survey (SKI) conducted by the Indonesian Ministry of Health, anemia is still a major health problem in Indonesia. The prevalence of anemia in women of childbearing age (15–49 years) was recorded at 27.2%. The most affected group is pregnant women with a prevalence of 48.9%, followed by adolescent girls at 32%. The main factors causing anemia in Indonesia include lack of iron intake, parasitic infections such as worms, and other chronic diseases. This condition can have an impact on academic performance, physical growth, and psychological well-being of female students. Based on these problems, community service activities were carried out at SMA Negeri 1 Meureubo through anemia counseling activities. The implementation time was on October 26, 2024. The target was female students of SMA 1 Meureubo